Marketing Communication Drivers of Adoption Timing of a New E-Service among Existing Customers - Prins, Remco; Verhoef, Peter C. (Journal of Marketing, 2007)
This study investigates the effects of direct marketing communications and mass marketing communications on the adoption timing of a new e-service among existing customers. The mass marketing communications pertain to both specific new service advertising and brand advertising from both the focal supplier and the competitors. Using a split-hazard approach, the authors determine the effects of the considered marketing communications on adoption timing, accounting for a significant part of the customer base that never adopts the new e-service. They analyze individual adoption behavior with a sample of 6000 customers of a Dutch telecommunications operator over 25 months. The empirical results show that service advertising shortens the time to adoption, even when it is initiated by competitors. Furthermore, an exploratory analysis of the interaction effects between relationship characteristics and marketing efforts suggests that certain mass marketing efforts have a greater effect on loyal customers.